The extended Planetary Nebula Spectrograph (ePN.S) early-type galaxy survey: The specific angular momentum of ETGs - Pulsoni Claudia; Gerhard Ortwin; Fall S. Michael; Arnaboldi Magda; Ennis Ana I.; Hartke Johanna; Coccato Lodovico; Napolitano Nicola R. (EDP SCIENCES S A, 2025)
Context. Mass and angular momentum are key parameters of galaxies. Their coevolution establishes an empirical relation between the specific stellar angular momentum j* and the stellar mass M* that depends on morphology.
Aims. For this work, we measured j* in a sample of 32 early-type galaxies (ETGs) from the ePN.S survey, using the full two-dimensional kinematic information. We present local λ profiles and projected j* profiles in apertures. We derived the distribution of these galaxies on the total j* − M* plane and determined the ratio between the stellar j* and the specific angular momentum of the host dark matter halo.
Methods. We used integral-field-spectroscopic data in the central regions (one to two effective radii, Re) and planetary nebula (PN) kinematics in the outskirts (out to a mean 6Re). In the j* determination, we accounted for misaligned rotation and for the differences between light-weighted j* and mass-weighted j*, estimating also the effects of gradients in the mass-to-light ratio driven by variations in the initial mass function. We used simulated ETGs from the IllustrisTNG simulation TNG100 to correct for the limited radial coverage of the PN data and to account for projection effects on j*.
Results. The radially extended, two-dimensional kinematic data show that the stellar halos of ETGs do not contain large stellar mass fractions of high j*. The j* profiles of fast-rotator ETGs are largely converged within the range of the data. For slow rotators, j* is still rising and is estimated to increase beyond 6Re by up to 40%, using simulated galaxies from TNG100. More than 60% of their stellar halo angular momentum is in misaligned rotation. We find that the ePN.S ETG sample displays the well-known correlation between j*, M*, and morphology: elliptical galaxies have systematically lower j* than similar mass S0 galaxies. However, fast and slow rotators lie on the same relation within errors with the slow rotators falling at the high M* end. A power-law fit to the mass-weighted j* − M* relation gives a slope of 0.55 ± 0.17 for the S0s and 0.76 ± 0.23 for the ellipticals, with normalization about four and nine times lower than spirals, respectively. The estimated retained fraction of angular momentum at 1010 ≤ M* ≤ 1010.5 M⊙ is ∼25% for S0s and >10% for ellipticals, and decreases by ∼1.5 orders of magnitude at M* ∼ 1012 M⊙.
Conclusions. Our results show that ETGs have substantially lower j* than spiral galaxies with similar M*. Their j* must be lost during their evolution, and/or retained in the hot gas component and the satellite galaxies that have not yet merged with the central galaxy.